2007
DOI: 10.1016/j.expneurol.2007.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Impaired antibody synthesis after spinal cord injury is level dependent and is due to sympathetic nervous system dysregulation

Abstract: Individuals with spinal cord injury (SCI) are highly susceptible to infection. This post-traumatic immune suppression is thought to occur via alterations in sympathetic nervous system (SNS) or hypothalamic-pituitary-adrenal (HPA) axis function. Normally, the HPA axis and SNS help coordinate proper immune function. After SCI, the HPA axis becomes activated and descending input to sympathetic preganglionic neurons (SPNs) is impaired. Because lymphoid organs are innervated by SPNs distributed throughout the thora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
217
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(234 citation statements)
references
References 58 publications
(64 reference statements)
13
217
0
Order By: Relevance
“…It is likely that CD-1 and C57BL/6 mice respond differently to SCI such that reducing neutrophils in the injured spinal cord is detrimental to CD-1 recovery, but beneficial to C57BL/6 recovery. Furthermore it has also been reported that the immune response triggered by SCI may be different for high thoracic SCI (as performed in our study) compared to lower thoracic SCI (as performed in the study by Stirling and associates), as higher levels of SCI (T3-T6) impair sympathetic innervation of lymphoid tissue (Lucin et al, 2007;Popovich and McTigue, 2009). …”
Section: Discussionsupporting
confidence: 57%
“…It is likely that CD-1 and C57BL/6 mice respond differently to SCI such that reducing neutrophils in the injured spinal cord is detrimental to CD-1 recovery, but beneficial to C57BL/6 recovery. Furthermore it has also been reported that the immune response triggered by SCI may be different for high thoracic SCI (as performed in our study) compared to lower thoracic SCI (as performed in the study by Stirling and associates), as higher levels of SCI (T3-T6) impair sympathetic innervation of lymphoid tissue (Lucin et al, 2007;Popovich and McTigue, 2009). …”
Section: Discussionsupporting
confidence: 57%
“…This is in contrast to previous work showing more severe effects after higher-level injuries on autonomic dysreflexia, inflammation, and cardiovascular problems. 16,66,67 Both injury levels used here, however, completely (cervical) or partially (thoracic) disrupt descending control of sympathetic neurons innervating the liver and, thus, differences in hepatic changes between cervical and thoracic injuries were subtle. To further test this, a cohort of animals received a lumbar SCI to spare sympathetic innervation to the liver.…”
Section: Sauerbeck Et Almentioning
confidence: 92%
“…There is ample evidence demonstrating that despite an elevated inflammatory state, SCI is associated with a state of immunosuppression and a heightened susceptibility to infection. [6][7][8][9] Suppressed function of natural killer cells, neutrophils, macrophages and lymphocytes have each been documented following SCI. 6,10,11 The loss of motor and sensory function also contribute to this population's greater susceptibility to a number of acute infections, including urinary tract infection (UTI) and pressure ulcers, as well as metabolic disorders associated with a more sedentary lifestyle such as obesity, atherosclerosis and type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…8 As lymphoid organs such as the spleen and adrenal gland are innervated by sympathetic neurons that originate from regions throughout the thoracolumbar spinal cord, an injury at or above this region may be expected to induce immune suppression. 9 Damage to the cervical spine would interfere with supraspinal control over preganglionic neurons below the injury, whereas damage at the mid-thoracic region would damage preganglionic sympathetic neurons directly. 7 Level-dependent impairment in B-cell function has been demonstrated in mice subjected to high (T3) versus mid-thoracic (T9) SCI.…”
Section: Introductionmentioning
confidence: 99%